The pH dependence of Am(III) complexation with acetate: an EXAFS study - Fröhlich, Daniel R.; Skerencak-Frech, Andrej; Bauer, Nicole; Roßberg, André; Panak, Petra (Journal of synchrotron radiation, 2015)
The complexation of acetate with Am(III) is studied as a function of the pH (1-6) by extended X-ray absorption fine-structure (EXAFS) spectroscopy. The molecular structure of the Am(III)-acetate complexes (coordination numbers, oxygen and carbon distances) is determined from the raw - k - 3 - -weighted Am - L - III - -edge EXAFS spectra. The results show a continuous shift of Am(III) speciation with increasing pH value towards the complexed species. Furthermore, it is verified that acetate coordinates in a bidentate coordination mode to Am(III) (Am—C distance: 2.82 ± 0.03 Å). The EXAFS data are analyzed by iterative transformation factor analysis to further verify the chemical speciation, which is calculated on the basis of thermodynamic constants, and the used structural model. The experimental results are in very good agreement with the thermodynamic modelling.